2019
DOI: 10.1093/cercor/bhz043
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Causal Modeling of the Relationship between Cognition and Theta–alpha Oscillations in Adults with Down Syndrome

Abstract: Individuals with Down syndrome (DS) show high inter-subject variability in cognitive ability and have an ultra-high risk of developing dementia (90% lifetime prevalence). Elucidating factors underlying variability in cognitive function can inform us about intellectual disability (ID) and may improve our understanding of factors associated with later cognitive decline. Increased neuronal inhibition has been posited to contribute to ID in DS. Combining electroencephalography (EEG) with dynamic causal modeling (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 69 publications
3
17
0
Order By: Relevance
“…During NREM sleep, cortical slow waves were shallower in TS mice while low gamma oscillations were amplified, further reflecting prolonged episodes of light sleep. In addition, NREM PFC-HPC theta phase synchronization was augmented compared to WTs, in concordance with previous EEG studies (43). Our observations of increased cortical activity and cross-regional synchronization during sleep in Ts65Dn mice may explain insomnia in DS, as recently suggested by studies in human subjects (47).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…During NREM sleep, cortical slow waves were shallower in TS mice while low gamma oscillations were amplified, further reflecting prolonged episodes of light sleep. In addition, NREM PFC-HPC theta phase synchronization was augmented compared to WTs, in concordance with previous EEG studies (43). Our observations of increased cortical activity and cross-regional synchronization during sleep in Ts65Dn mice may explain insomnia in DS, as recently suggested by studies in human subjects (47).…”
Section: Discussionsupporting
confidence: 92%
“…During quiet wakefulness, spiking activity and theta power in the PFC and HPC were increased in TS mice. Cortical theta oscillations are associated with working memory and cognitive flexibility (40)(41)(42) and are augmented in adults with DS (43). These large prefrontal theta oscillations predicted poor memory performance in TS mice and were reduced by EGCG.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, due to the facts mentioned above, the simultaneous causal interaction between bilateral gait was taken into account for purposes of analysis in this study. (2) As is widely known, time series observed in nature usually contain oscillatory components within a specific frequency band [36], [37]. For physiological signals, such as electroencephalography, their Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In Scz, self-inhibition and cognition were only associated – in the 40 Hz ASSR – in R A1. Interestingly, a rsEEG DCM study in Down syndrome (n=36) found intelligence was associated with self-inhibition in V1 33 . Why is unclear: self-inhibition may be estimated more efficiently in sensory regions.…”
Section: Discussionmentioning
confidence: 99%